CULTURAL EXPLORATION AS ALTER/NATIVE1 ROUTE TO NATIONAL DEVELOPMENT: INSIGHTS FROM YORUBA VERBAL ARTS - OLUWOLE COKER; ADESINA COKER (KEMANUSIAAN: The Asian Journal of Humanities, 2009)
This paper interrogates Yoruba verbal arts and situates culture as a catalyst for development. It is suggested that the intricate resources of oral art, exemplified by Yoruba textual references, are viable ingredients for socio-cultural empowerment. To fully comprehend the dynamics of a society in constant change due to external and internal realities, one must reconsider culture in order to reposition the society. The multidimensional and multidisciplinary significance of Yoruba verbal art demonstrate that culture has a vital role to play in any meaningful socio-political advancement in the Nigerian body polity. The ideas conveyed in proverbial expressions, representing key cultural realities of the Yoruba people, offer insights and ideas for development and social good. The paper submits that a deeper exploration of the intricate resources of verbal art is a viable route to development.